Studies on the redox centers of the terminal oxidase from Desulfovibrio gigas and evidence for its interaction with rubredoxin - Gomes, Cláudio (2009)
Abstract: Rubredoxin-oxygen oxidoreductase (ROO) is the final component of a soluble electron transfer chain that couples NADH oxidation to oxygen consumption in the anaerobic sulfate reducer Desulfovibrio gigas. It is an 86-kDa homodimeric flavohemeprotein containing two FAD molecules, one mesoheme IX, and one Fe-uroporphyrin I per monomer, capable of fully reducing oxygen to water. EPR studies on the native enzyme reveal two components with g values at similar to 2.46, 2.29, and 1.89, which are assigned to low spin hemes and are similar to the EPR features of P-450 hemes, suggesting that ROO hemes have a cysteinyl axial ligation. At pH 7.6, the flavin redox transitions occur at 0 +/- 15 mV for the quinone/semiquinone couple and at -130 +/- 15 mV for the semiquinone/hydroquinone couple; the hemes reduction potential is -350 +/- 15 mV. Spectroscopic studies provided unequivocal evidence that the flavins are the electron acceptor centers from rubredoxin, and that their reduction proceed through an anionic semiquinone radical. The reaction with oxygen occurs in the flavin moiety. These data are strongly corroborated by the finding that rubredoxin and ROO are located in the same polycistronic unit of D. gigas genome. For the first time, a clear role for a rubredoxin in a sulfate-reducing bacterium is presented.